Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1471-2393-14-134
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum trend in blood pressure levels, renal function and proteinuria in women with severe preeclampsia and eclampsia in Sub-Saharan Africa: A 6-months cohort study

Abstract: BackgroundPreeclampsia and eclampsia, which are the most frequent hypertensive disorders in pregnancy, are associated with renal involvements. We aimed to assess the time trend in blood pressure levels, renal function and proteinuria after delivery, and investigate their determinants in Cameroonian women with severe preeclampsia and eclampsia.MethodsThis was a prospective cohort study involving 54 women with severe preeclampsia and eclampsia, conducted between July 2010 and February 2012 at the central materni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 23 publications
8
60
6
Order By: Relevance
“…The present study could have overestimated the incidence of persistent hypertension owing to the relatively short follow‐up (up to 6 weeks after delivery). The incidence of persistent hypertension following pre‐eclampsia has been demonstrated to decrease over time; in a previous study [17] persistent hypertension rates of 42.6%, 27.8%, and 14.8% were recorded at 6 weeks, 3 months, and 6 months after delivery, respectively. Persistent hypertension following pre‐eclampsia could be unrepresentative of the wider community because the patients included in these studies (pregnant women) undergo regular medical follow‐up, and similar rates of hypertension could be undetected among groups of individuals who are not monitored as closely, such as male patients and non‐pregnant women.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present study could have overestimated the incidence of persistent hypertension owing to the relatively short follow‐up (up to 6 weeks after delivery). The incidence of persistent hypertension following pre‐eclampsia has been demonstrated to decrease over time; in a previous study [17] persistent hypertension rates of 42.6%, 27.8%, and 14.8% were recorded at 6 weeks, 3 months, and 6 months after delivery, respectively. Persistent hypertension following pre‐eclampsia could be unrepresentative of the wider community because the patients included in these studies (pregnant women) undergo regular medical follow‐up, and similar rates of hypertension could be undetected among groups of individuals who are not monitored as closely, such as male patients and non‐pregnant women.…”
Section: Discussionmentioning
confidence: 93%
“…However, lower rates of persistent hypertension have been reported in Uganda (28%) [8] and among patients in an American study [16] that found 21% of patients with severe pre‐eclampsia experienced persistent hypertension 6 weeks after delivery. Conversely, a study in Cameroon reported that 42.6% of patients with severe pre‐eclampsia had persistent hypertension 6 weeks after delivery [17].…”
Section: Discussionmentioning
confidence: 94%
“…Normalization of proteinuria should occur at up to 6 months after delivery among women with pre‐eclampsia; however, proteinuria or hypertension can persist for as long as 24 months postpartum. Women who presented with pre‐eclampsia and remain proteinuric after 6 months of delivery should be assessed for underlying chronic kidney disease …”
Section: Discussionmentioning
confidence: 99%
“…Women who develop PE are at a greater risk of cardiovascular and cerebrovascular events even years after their pregnancies. Despite this risk, few studies have focused on the recovery course of HDP . Indeed, data of post‐partum recovery of HDP is limited, particularly in China.…”
Section: Introductionmentioning
confidence: 99%